KARAKTERISTIK DAN FUNGSI BAHASA DALAM IKLAN APLIKASI BELANJA ONLINE - Adisti Anastasya Oktaviani; Aura Naila Syalvia (Universitas Madura, 2021)
Each language must have its own characteristics according to the use by the speaker to meet the needs in the use of language to communicate. In communicating, language has various functions that are adapted to what the purpose of communication is. The purpose of this study was to analyze the characteristics of the language used in online shopping application advertisements and the language function of the use in online shopping application advertisements. This research is interesting to study because it discusses various language characteristics and language functions used in various online shopping applications such as Shopee, Tokopedia, Bukalapak, and Akulaku shopping applications. The method in this study uses a qualitative approach. The data in this study are in the form of online shopping application advertisements found on social media. data collection using recording and note-taking techniques. Data were obtained by observing video recordings and then recording the data needed in this study. The results of this study are the characteristics in the use of online shopping advertising language on social media such as the use of regional languages, slang, and foreign languages. The language functions used in online shopping advertisements that we found were informative functions, directive functions, reminder functions, and expressive functions.